New aesthetic thought, methodology, and structure of systemic philosophy - Wu, Jie, 1934- (Advances in religious and cultural studies (ARCS) book series., 2020)
""This book proposes a new definition of aesthetics and discusses the connotation and structure of natural beauty, artistic beauty, and design beauty"--Provided by publisher"--